2022
DOI: 10.1038/s41574-022-00747-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of insufficient sleep and circadian misalignment in obesity

Abstract: Traditional risk factors for obesity and the metabolic syndrome, such as excess energy intake and lack of physical activity, cannot fully explain the high prevalence of these conditions. Insufficient sleep and circadian misalignment predispose individuals to poor metabolic health and promote weight gain and have received increased research attention in the past 10 years. Insufficient sleep is defined as sleeping less than recommended for health benefits, whereas circadian misalignment is defined as wakefulness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(102 citation statements)
references
References 202 publications
1
93
0
8
Order By: Relevance
“…However, the difference is that in our study, the cut-off value of CVAI was higher, which may be due to the fact that our study subjects were steelworkers. It has been shown that steelworkers have a higher prevalence of overweight and obesity than the general population due to their special occupational factors such as shift work, noise, and occupational stress in their production and living environment [ 46 , 47 , 48 ]. In addition, most of the steelworkers are middle-aged men.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference is that in our study, the cut-off value of CVAI was higher, which may be due to the fact that our study subjects were steelworkers. It has been shown that steelworkers have a higher prevalence of overweight and obesity than the general population due to their special occupational factors such as shift work, noise, and occupational stress in their production and living environment [ 46 , 47 , 48 ]. In addition, most of the steelworkers are middle-aged men.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike physical activity or nutrition, there is still a lack of understanding regarding how to utilize or correct biological timing for health bene ts 44,45 . Current public health interventions are largely focusing on increasing physical activity levels or eating healthy, with less attention on targeting the clock.…”
Section: Discussionmentioning
confidence: 99%
“…Shift work and certain sleep disorders like insomnia, obstructive sleep apnea, and reduced sleep and other factors like jet lag and timing of food intake can cause a state of circadian disruption, which increases the risk of developing metabolic and cardiovascular diseases [ 64 , 65 , 66 , 67 , 68 , 69 ]. For instance, clock genes are expressed cell-autonomously that receive projections from the suprachiasmatic nucleus (SCN); thus, it is possible that oscillation of key transcripts important in the response to anorexigenic and orexigenic hormones may be subject to circadian control [ 17 , 70 ].…”
Section: Discussionmentioning
confidence: 99%